2014
DOI: 10.1037/a0034822
|View full text |Cite
|
Sign up to set email alerts
|

Is it better to be average? High and low performance as predictors of employee victimization.

Abstract: Given increased interest in whether targets' behaviors at work are related to their victimization, we investigated employees' job performance level as a precipitating factor for being victimized by peers in one's work group. Drawing on rational choice theory and the victim precipitation model, we argue that perpetrators take into consideration the risks of aggressing against particular targets, such that high performers tend to experience covert forms of victimization from peers, whereas low performers tend to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 83 publications
(134 reference statements)
6
70
0
Order By: Relevance
“…Several studies note victims' social status and support play a role in victimization as well (e.g., Aquino & Bommer, ; Aquino et al, ). As a case in point, Jensen, Patel, and Raver () highlight a wealth of research suggesting those of lower standing are perceived as easier targets because they lack the resources necessary to counter attacks directed at them. Similarly, Hodges, Malone, and Perry () highlight children lacking friends to support them in the event of attacks are victimized more, a finding illustrated in various work contexts as well (Aquino & Thau, ; Hoel et al, ; Hogh & Viitasara, ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies note victims' social status and support play a role in victimization as well (e.g., Aquino & Bommer, ; Aquino et al, ). As a case in point, Jensen, Patel, and Raver () highlight a wealth of research suggesting those of lower standing are perceived as easier targets because they lack the resources necessary to counter attacks directed at them. Similarly, Hodges, Malone, and Perry () highlight children lacking friends to support them in the event of attacks are victimized more, a finding illustrated in various work contexts as well (Aquino & Thau, ; Hoel et al, ; Hogh & Viitasara, ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…The second explanation is that being perceived as threatening by others poses danger to individuals' relative standing or security, provoking them to attack the provocative victim to neutralize or eliminate the threat (Olweus, , ). For example, Jensen et al (, p. 298) find support for their logic that since “rate‐busting” high performers threaten to raise expectations of what is possible on the job, “coworkers are motivated to [attack them in an effort to] maintain the work group's current performance expectations, solidarity, and their individual positive self‐regard”; as such, high performers suffer more attacks aimed at hindering their relative productivity (e.g., sabotage; withholding needed resources). Across multiple studies and contexts, Kim and Glomb (, ) find support for similar arguments that higher ability people evoke negative reactions (e.g., resentment; envy) and threaten others relative standing to such an extent that these individuals are subject to more attacks as well.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Thus, in line with our previous discussion of the dimensions on which discrimination can vary, a pressing issue to consider is the degree to which perpetrators intend to discriminate (e.g., perhaps, the well-intentioned are unaware, or the illintentioned are too busy regulating their overt behaviors to be aware of their subtle ones). Indeed, research on victimization (Jensen, Patel, & Raver, 2014) and incivility (Cortina, 2008) suggests that discrimination, at times, can be subtle but also conscious and intentional. For example, Jensen and colleagues (2014) found that much of the covert victimization reported by employees targeted for overachieving was perceived to be both subtle and intentional, such as the intentional withholding of information and exclusion from team tasks.…”
Section: Perpetrator Experience Of Subtle Discriminationmentioning
confidence: 99%
“…Employees reported how often they had been the target of a series of behaviors enacted by their group members during the previous 30 days. These 10 items emerged from exploratory and confirmatory factor analyses of Glomb"s (2002) original 20-item scale [28].…”
Section: Methodsmentioning
confidence: 99%